2003
DOI: 10.1186/1471-244x-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Directional and fluctuating asymmetry in finger and a-b ridge counts in psychosis: a case-control study

Abstract: Background: Several studies have reported alterations in finger and a-b ridge counts, and their derived measures of asymmetry, in schizophrenia compared to controls. Because ridges are fully formed by the end of the second trimester, they may provide clues to disturbed early development. The aim of this study was to assess these measures in a sample of patients with psychosis and normal controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Minor directional asymmetry is present in some of the palmar and finger ridge counts [82,83,96]. Moreover, males have about 21 more ridges, on average, than females [45], though the effect size is small (Cohen's d = 0.36).…”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Minor directional asymmetry is present in some of the palmar and finger ridge counts [82,83,96]. Moreover, males have about 21 more ridges, on average, than females [45], though the effect size is small (Cohen's d = 0.36).…”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
“…Palmer and Strobeck [8], in an influential paper, concluded that the correlation of R on L behaves differently from all other indices and never achieves their statistical power. Nevertheless, both the correlation coefficient and coefficient of indetermination were still in wide use five years ago, especially by those studying human dermatoglyphic asymmetry (see [40,95,96,99]). …”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
“…Fluctuating asymmetry, for example, is associated with male, but not female, sexual orientation [325]. Moreover, it is positively associated with schizophrenia [326,327], human reactive aggression [328], and attention-deficit hyperactivity disorder [329,330], but is unrelated to psychosis [331].…”
Section: Anthropology and Evolutionary Psychologymentioning
confidence: 99%
“…For instance, for TFRC, the differences between patient and control groups have been found to be both statistically significant 1,6 and statistically insignificant. 9,10,27,29,30 Inconsistent results have also been obtained for AB-TRC.…”
Section: Determining the Association Between Dermatoglyphics And Schimentioning
confidence: 52%